Determination of convective heat transfer coefficient of various crops under open sun drying conditions - Togrul, IT (Pergamon-Elsevier Science Ltd, 2003)
In this study an attempt has been made to evaluate the convective heat transfer coefficient operating in crop drying in open still dryint conditions (natural convection). Values of the constant, C and n were obtained by linear regression analysis front experimental data obtained for nine crops, namely marrow, aubergine, carrot, green bean, albanian pepper, green pepper, potato. onion and pear. Based oil the values of C anti n convective heal transfer coefficients [for these crops were determined. We observed that the valves of convective heat transfer coefficient varied front crop to crop with a range of 0.25-3.3 W/m(2) degreesC for the crops studied. The data have also been analysed in terms of percent uncertainty. (C) 2003 Elsevier Science Ltd.
Keywords: Mass-Transfer Relations; Grain